Weight cycling exacerbates glucose intolerance and hepatic triglyceride storage in mice with a history of chronic high fat diet exposure - Miriam Bernecker; Anna Lin; Annette Feuchtinger; Anna Molenaar; Sonja C. Schriever; Paul T. Pfluger (Journal of Translational Medicine)
Abstract Background Obese subjects undergoing weight loss often fear the Yoyo dieting effect, which involves regaining or even surpassing their initial weight. To date, our understanding of such long-term obesity and weight cycling effects is still limited and often based on only short-term murine weight gain and loss studies. This study aimed to investigate the long-term impacts of weight cycling on glycemic control and metabolic health, focusing on adipose tissue, liver, and hypothalamus. Methods Chow-fed mice and mice subjected to prolonged high-fat diet (HFD) consumption for 20 weeks, followed by 24 weeks of dietary interventions to either induce weight gain, weight loss, or weight cycling were monitored for perturbations in feeding efficiency and glucose homeostasis. Post-mortem analyses included qPCR, Western Blotting, biochemical and microscopical assessments for hepatic steatosis and insulin resistance, hypothalamic and adipose tissue inflammation, and circulating lipid, leptin and IL-6 levels. Results Weight cycling led to hyperphagia and rapid weight regain, matching the weights of mice continuously on HFD. Despite weight loss, adipose tissue inflammation persisted with elevated pro-inflammatory markers, macrophage infiltration, and impaired Glut4 expression. HFD-induced dysregulation in hypothalamic expression of orexigenic peptides and synaptic plasticity markers persisted also after weight normalization suggesting long-lasting neural alterations. Weight-cycled mice exhibited higher circulating IL-6 and leptin levels, increased hepatic lipid storage, and dysregulated glucose metabolism compared to those with consistent diets, indicating worsened metabolic effects by Yoyo dieting. Conclusion In sum, our study highlights significant metabolic risks associated with weight cycling, particularly following prolonged obesity. Persistent adipose tissue inflammation, perturbed neural peptide and plasticity markers and impaired glucose tolerance emphasize the need for effective and sustainable weight loss strategies to mitigate the adverse outcomes of weight regain and improve long-term metabolic health.